Combustion stability study of partially premixed combustion by high-pressure multiple injections with low-octane fuel. (15th August 2019) - An, Yanzhao; Tang, Qinglong; Vallinayagam, Raman; Shi, Hao; Sim, Jaeheon; Chang, Junseok; Magnotti, Gaetano; Johansson, Bengt
Highlights: The minimum intake air temperature was reduced from 70 °C to 50 °C for stable partially premixed combustion by using a multiple-injection strategy. As compared to a single injection strategy, the indicated mean effective pressure increased by 24% for optimized triple-injections with an injection pressure of 800 bar with the same amount of fuel. The variation of unburned hydrocarbon emission with respect to different injection timing was linked to in-cylinder combustion and explained by spray/wall interaction, fuel-trapping in piston crevice. Abstract: This work is the second part of a study on low-load combustion stability for gasoline partially premixed combustion. In part 1, we investigated the sensitivity of the intake air temperature to combustion stability. In part 2, we evaluate the potential of the multiple-injection strategy along with the intake air temperature sensitivity to promote low-load combustion stability using low-octane gasoline fuel. The experiments were carried out in a fully transparent, single-cylinder, compression-ignition engine. The spray/wall interaction, particularly the fuel trapping in the piston crevice zone, was visualized by fuel-tracer planar laser-induced fluorescence for the first time in experiments. The in-cylinder combustion process of natural flame luminosity was captured by a high-speed color camera. By employing a multiple-injection strategy, the minimum intake air temperature can be further reduced from 70 °C (single injection) to 50 °C for target stable combustion. The combustion stability and engine performance were further improved by increasing the fuel injection pressure. For instance, with the triple-injection strategy at a higher fuel-injection pressure of 800 bar, the indicated mean effective pressure was increased by 24% when compared to that of the single-injection strategy. A stronger interaction among fuel spray jets, the piston, and the cylinder wall was observed for multiple injections with higher injection pressure, leading to higher unburned hydrocarbon (UHC) and carbon monoxide (CO) along with a more pronounced pool fire in the squish zone. The double-injection strategy resulted in lower UHC and CO emissions when compared to the triple-injection strategy. Applying a narrow spray angle injector with re-entrant combustion chamber is suggested for optimizing the spray/wall interaction.